2014 Makassar International Conference on Electrical Engineering and Informatics (MICEEI) 2014
DOI: 10.1109/miceei.2014.7067314
|View full text |Cite
|
Sign up to set email alerts
|

Ultra Wide Band (UWB) antenna design for fetal monitoring

Abstract: UWB microstrip antenna has been designed using UWB technology and the principle of Microwave Imaging system that works at UWB frequencies. The Simulation performed using Ansoft HFSS version 13 software to construct the microstrip antenna with some important parameters, such as reflection coefficient (SII) and radiation pattern. This purpose of the antenna is fetal detecting and monitoring system in dual band at (2.54 -4.45) GHz with the bandwidth of 1.91 GHz and (6.53 -7.97) GHz with the bandwidth of 1.44 GHz.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The research results are presented in the current scientific paper is the advanced studies of the previous one reported in [1]. Several optimization steps on the last fetal monitoring system prototype were performed including the UWB microstrip antenna and the RF processing configuration [1].…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…The research results are presented in the current scientific paper is the advanced studies of the previous one reported in [1]. Several optimization steps on the last fetal monitoring system prototype were performed including the UWB microstrip antenna and the RF processing configuration [1].…”
Section: Introductionmentioning
confidence: 93%
“…Fig. 2 below shows the dimension of the antenna that has been optimized referred to the previous antenna design parameters [1]. …”
Section: A the Antenna Numerical Designmentioning
confidence: 99%
See 3 more Smart Citations